The Effect of Nurse Staffing Ratios on Status of Patient Outcome in Emergency Unit at Dr. Lorenzo P. Ziga Memorial District Hospital - Branuelo, Jolly; Alcala, Emerlinda (International Journal of Sustainability and Advanced Integrated Research, 2026)
Nurse staffing shortages in Philippine emergency rooms, particularly at ratios exceeding 1:30, compromise patient outcomes through increased burnout, medical errors, and dissatisfaction, as evidenced by global and local studies highlighting the need for optimal staffing to enhance care quality. This descriptive correlational study examined nurse-to-patient ratios in the Emergency Room of Dr. Lorenzo P. Ziga Memorial District Hospital, Tabaco City, Albay, and their relationship to patient outcomes including mortality rates, complications, satisfaction scores, and length of stay, surveying 50 emergency room nurses and 100 patients using validated questionnaires and hospital records analyzed through Pearson’s r and chi-square tests (p<0.05). Findings revealed predominant ratios of 1:15 daytime and 1:25 nighttime, with strong negative correlations between optimal ratios and complications (r=-0.62), mortality risk (r=-0.58), and length of stay (r=-0.55), alongside positive associations with patient satisfaction (r=0.71), moderated by nurse burnout that exacerbated adverse effects at higher ratios. Lower nurse-to-patient ratios significantly improve emergency room patient outcomes, warranting mandated 1:12 ratios, targeted burnout interventions, and policy alignment with Republic Act No. 9173 to enhance staffing standards and care delivery.